Kewenangan Penyidik Pegawai Negeri Sipil (PPNS) dalam Undang-Undang Republik Indonesia No.8 Tahun 1981 tentang Hukum Acara Pidana pada Pasal 1 Ayat (1) Jo. Pasal 6 Ayat (1) dan Undang-Undang No.19 Tahun 2019 tentang Tindak Pidana Korupsi pada Pasal 1 Ayat (6) dalam Proses Peradilan Pidana Indonesia - Abdul Hayy Nasution; I Gusti Ayu Anita Lakshana (FOCUS, 2022)
Law No. 8 of 1981 concerning the Criminal Procedure Code (KUHAP) Article 1 paragraph (10) states that an investigator is a State Police Officer of the Republic of Indonesia or certain Civil Servant Officers who are given special authority by law to conduct investigations. And it is emphasized again in Article 6 paragraph (10) letter b which reads that investigators are certain Civil Servant officials who are given special authority by law. The scope of Civil Servant Investigators (PPNS) in Corruption Crimes, in Law No.19 of 2019, Article 69B paragraph (1), (2) and Article 69C, which reads as follows: "Article 69b paragraph (1); when this Law comes into force, investigators or investigators from the Corruption Eradication Commission have not been registered as employees of the state civil apparatus within a maximum period of 2 (two) years after this Law comes into force, they may be appointed as employees of the state civil apparatus as long as they comply with the provisions of laws and regulations. invitation.